A Comparison of Perceptions of Reassurance in Patients with Nontraumatic Neck Pain and Whiplash-Associated Disorders in Consultations with Primary Care Practitioners—An Online Survey. Issue 12 (8th October 2020) - Silva Guerrero, Alma Viviana; Setchell, Jenny; Maujean, Annick; Sterling, Michele
Abstract: Objectives: Neck pain remains highly prevalent and costly worldwide. Although reassurance has been recommended as a first line of treatment, specific advice on the best ways to provide reassurance has not been provided due to lack of evidence. Pain symptoms and experiences differ between patients with whiplash-associated disorder (WAD) and those with nontraumatic neck pain (NTNP). The aims of this study were to 1) identify and compare the concerns, fears, and worries of patients with WAD and NTNP; and 2) determine if patients believe their concerns are addressed by primary care providers. Methods: These questions were investigated through an online survey, with a convenience sample of 30 participants with NTNP and 20 with WAD. Results: A thematic analysis of survey responses resulted in the following seven themes related to common concerns, and two regarding how well concerns were addressed. Common concerns expressed by both groups shared four themes: 1) further structural damage, 2) psychological distress, 3) concerns about the future, and 4) hardships that eventuate. Theme 5), pain/disability is long term, was specific to WAD. Themes 6), pain is current or reoccurring, and 7), interference with daily life, were specific to NTNP. Regarding how well patient concerns were addressed, two overarching themes were common to both conditions: 1) concerns were addressed, with both groups sharing the subthemes "successful treatment, " "reassurance, " and "trust"; and 2) concerns were not addressed, where all subthemes were shared with the exception of two unique to NTNP. Conclusions: This detailed comparison provides information about neck pain patients' concerns and fears, while providing health practitioners support for selecting strategies to promote reassurance appropriately for individual patient needs. Our findings from patients' perspectives enhance the understanding for providing reassurance for neck pain as proposed by our analysis.